Medical Tourism in Germany Determinants of International Patients' Destination Choice - Schmerler, Klaus (Developments in Health Economics and Public Policy,, 2018)
This book examines the drivers of inbound medical tourism in Germany. In light of growing international trade of medical services, it provides a quantitative analysis of the determinants of international patients' choice of destination. It develops coherent definitions of medical tourism and medical travel, and presents multiple unique data sets to identify inbound medical travelers in Germany. Further, it introduces an empirical modeling framework for investigating and quantifying the drivers and effects of a patient's choice of destination at the national, hospital and individual level. A particular focus of the analysis lies on cultural proximity and personal networks as key channels to convey trust in a destination's service. In addition, real consideration sets of international patients are presented. The findings presented are embedded in a global context and will help inform future empirical investigations and modeling.